2022
DOI: 10.3847/1538-4357/ac60a2
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiar Short-duration GRB 200826A and Its Supernova*

Abstract: Gamma-ray bursts (GRBs) are classified into long and short events. Long GRBs (LGRBs) are associated with the end states of very massive stars, while short GRBs (SGRBs) are linked to the merger of compact objects. GRB 200826A was a peculiar event, because by definition it was an SGRB, with a rest-frame duration of ∼0.5 s. However, this event was energetic and soft, which is consistent with LGRBs. The relatively low redshift (z = 0.7486) motivated a comprehensive, multiwavelength follow-up campaign to characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 148 publications
0
38
0
Order By: Relevance
“…The fraction of long GRBs that are accompanied by a SN is still debated. Rossi et al (2022b) found that for over 1400 long GRBs discovered by Swift through 2022, only 40-50 of them have associated SNe identified via a bump in the optical light curve, and 28 have spectroscopic confirmation. Dado & Dar (2018) found that for low redshifts, the number of GRBs with associated SNe are comparable to GRBs without SNe.…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of long GRBs that are accompanied by a SN is still debated. Rossi et al (2022b) found that for over 1400 long GRBs discovered by Swift through 2022, only 40-50 of them have associated SNe identified via a bump in the optical light curve, and 28 have spectroscopic confirmation. Dado & Dar (2018) found that for low redshifts, the number of GRBs with associated SNe are comparable to GRBs without SNe.…”
Section: Introductionmentioning
confidence: 99%
“…Their ME phases are listed independently in Group B. The properties of GRB 200826A and GRB 100816A are similar to those of typical LGRBs, and it has been confirmed that GRB 200826A is associated with an SN (Ahumada et al 2020(Ahumada et al , 2021Zhang et al 2021;Rossi et al 2022). They are suggested as short LGRBs.…”
Section: Sample Selection and Analysismentioning
confidence: 80%
“…LGRBs locate in host galaxies with active star formation and in areas with a high star formation rate (SFR) or specific star formation rate (SSFR; i.e., SFR per unit mass), while SGRBs preferentially locate in elliptical or early-type galaxies or in areas with a low SSFR (Zhang et al 2009). However, there are still some special cases, such as long-duration bursts with short-burst characteristics (long SGRBs; e.g., GRB 060614: Gehrels et al 2006;Jin et al 2015;Yang et al 2015;and GRB 211211A: Gompertz et al 2023;Rastinejad et al 2022;Yang et al 2022) and short-duration bursts with long-burst characteristics (short LGRBs; e.g., GRB 040924: Fan et al 2005;and GRB 200826A: Ahumada et al 2021;Zhang et al 2021;Rossi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the short GRBs likely arise from the merger of compact objects, as evidenced by the presence of kilonova emission in their light curves (Berger et al 2013;Tanvir et al 2013;Gompertz et al 2018;Lamb et al 2019;Rastinejad et al 2021), and most robustly by their association with a gravitational wave signal (Abbott et al 2017). Although it should be noted that there is clearly a more significant overlap in the progenitors of long and short GRBs than previously realized, with SNe in some short GRBs (Ahumada et al 2021;Rossi et al 2022), and kilonovae in bursts with durations in excess of a minute (Mei et al 2022;Rastinejad et al 2022;Troja et al 2022;Yang et al 2022). GRBs have been used as probes of extreme physics, routes to understanding stellar evolution and as lighthouses to the distant universe.…”
Section: Introductionmentioning
confidence: 92%